FLORAE MALESIANE PRAECURSORES XLIX. MALESIAN SPECIES OF LITHOCARPUS BL(FAGACEAE) - E. SOEPADMO (REINWARDTIA, 1970)
Lithocarpus Bl. (1826) is here considered to include the following genera: Synaedrys Lindl. (1836), Cyclobalanus (Endl.) Oersted (1867, p.p.),and Pasania (Miq.) Oersted (1867, p.p.).In Malesia 104 species are recognized, of which 25 are new to science and 7 are new combinations.Apart from these there are 10 more species which are considered as doubtful,as from the specimens so far examined it is difficult to decide their correct status. Pasania littoralis (Bl.) Oersted (basionym: Quercus littoralis Bl.)is excluded from the genus, and the species has been reidentified by Dr. A.J.G.H.Kostermans (Bogor) as Atuna scabra (Hassk.)Kosterm.In Malesia most species of Lithocarpus may be distinguished from those of Castanopsis by the ridged inner surface of their bark, uniseriate and multiseriate wood-rays,spiral arrangement of leaves and bud-scales,and by their cupule which always encloses one fruit only, and which are solitary or in dichasial clusters along the rachis, possessing interseminal cupule segments and a scattered pattern of vascularization.